Effects of financial inclusion of small and medium-sized enterprises on financial stability: evidence from selected sub-Saharan African countries - Moeti Damane; Sin Yu Ho (Journal of Innovation and Entrepreneurship)
Abstract This study investigates the impact of SME financial inclusion on financial stability in 11 sub-Saharan African countries from 2005 to 2019. Using fixed effects estimation with Driscoll and Kraay standard errors and a fixed effect panel quantile regression model, the findings align with the excessive financial inclusion theory, showing that SME financial inclusion, measured by SME depositors with commercial banks, negatively impacts financial stability, with the effect intensifying at higher stability levels. To mitigate these risks, it is recommended that banks diversify their deposit base, financial regulators incorporate bank-run vulnerability into stability assessments, and ensure financial institutions maintain adequate capital levels.